Um estudo sobre a função exponencial - Oliveira, Rafael Henrique de [UNESP] (2015)
We conducted a study of the exponential function, analysing the main properties of this function and the construction of its graph. For this, a detailed research on some subset of the real numbers was carried out, providing the basis for understanding the properties involved in the potentiation of a real number. At the end of the work, we highlight some applications of the exponential function, which can serve as motivation to start teaching this in basic education in Brazil